Analisis Displacement Struktur Beton Tinggi Pada Gedung Universitas - Tjahjono, Budi (CV. SINAR HOWUHOWU, 2024)
This study aims to evaluate the seismic resilience of STKIP Santo Paulus Ruteng building using the SNI 1726:2019 standard. The research methodology employs displacement analysis to calculate maximum building displacements in two directions, X and Y, considering displacement amplification and building importance factors. The analysis results demonstrate that the building meets the seismic resilience requirements under static equivalent earthquake loads, with maximum displacements on the highest floor reaching 45.3 mm (X direction) and 18.42 mm (Y direction). This research contributes to ensuring the structural safety of tall buildings in seismic-prone areas